Towards an Automatic Strategy for Acquiring the WordNert.Br Hierarchical Relations - Di Felippo, Ariani; Dias-da-Silva, Bento Carlos (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2007: Anais do V Workshop em Tecnologia da Informação e da Linguagem Humana, 2007)
This paper outlines an “automatic strategy with post-editing” for specifying the Brazilian Portuguese WordNet (WordNet.Br) hierarchical lexical-conceptual relations (taxonomies and meronymies). It relies on a two-step analysis: (a) the computer-aided linking (lexical-conceptual alignment) of the WordNet.Br synsets to the their semantically equivalent ones in the Princeton WordNet; (b) the automatic transfer with post-editing of the relevant hierarchical relations spotted by the previous step.